ZAMONAVIY TA’LIMDA “4 K” YONDASHUVI AMALIYOTINI SINGDIRISHNING BA’ZI MASALALARI - Aslanova , Nozima Khakimovna (Educational Research in Universal Sciences, 2023)
Today’s education supports the practice of collecting free ideas and opinions expressed by learners on a small problem, and through them, renewing the methods to arrive at solutions. The article presents issues of education renewal.